2012
DOI: 10.1371/journal.pone.0050664
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Pyrosequencing of the Parasitoid Wasp Cotesia vestalis: Genes Involved in the Antennal Odorant-Sensory System

Abstract: Cotesia vestalis is an endoparasitic wasp that attacks larvae of the diamondback moth (Plutella xylostella), a herbivore of cruciferous plants. Females of C. vestalis use herbivore-induced plant odorants released from plants infested by P. xylostella as a host-searching cue. Transcriptome pyrosequencing was used to identify genes in the antennae of C. vestalis adult females coding for odorant receptors (ORs) and odorant binding proteins (OBPs) involved in insect olfactory perception. Quantitative gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…also shared similarity with proteins from other hymenopterans, including Camponotus floridana, Apis florea, Bombus terrestri, Acromyrmex echinatior, Apis mellifera, Solenopsis invicta, and Nasonia vitripennis. Similar trends in protein similarity were reported for the transcriptome analyses of the parasitoid wasps, Cotesia vestalis and Spalangia endius (Nishimura et al, 2012;Zhang et al, 2014).…”
Section: Overview Of Antennal Transcriptome Of Sclerodermus Spsupporting
confidence: 79%
See 2 more Smart Citations
“…also shared similarity with proteins from other hymenopterans, including Camponotus floridana, Apis florea, Bombus terrestri, Acromyrmex echinatior, Apis mellifera, Solenopsis invicta, and Nasonia vitripennis. Similar trends in protein similarity were reported for the transcriptome analyses of the parasitoid wasps, Cotesia vestalis and Spalangia endius (Nishimura et al, 2012;Zhang et al, 2014).…”
Section: Overview Of Antennal Transcriptome Of Sclerodermus Spsupporting
confidence: 79%
“…2, the distribution of unigenes annotated as molecular function showed that the genes expressed in the antennae were primarily related to binding activity (6545 unigenes, 46.19%), whereas 1236 (8.72%) of the unigenes were involved in transporter activity. Similar trends in GO annotation were also observed in the transcriptomic analyses of C. vestalis and N. vitripennis (Nishimura et al, 2012;Pannebakker et al, 2013).…”
Section: Overview Of Antennal Transcriptome Of Sclerodermus Spsupporting
confidence: 77%
See 1 more Smart Citation
“…To better understand the sophisticated olfactory system of C. pallens , 66 putative chemoreception genes(including OBPs , CSPs , ORs , IRs , and SNMPs ) were identified from our transcriptome. This number is more than the numbers found in Cnaphalocrosis medinalis (22) [41] and Cotesia vestalis (28) [42], but less than that of Spodoptera littoralis (82) [30], Manduca sexta (94) [43] and Helicoverpa armigera (99) [34].…”
Section: Discussionmentioning
confidence: 64%
“…These genetic samples are collected from multiple tissue types (e.g., muscle, heart, liver), and preserved cryogenically or in a fixative that slows degradation (e.g., ethanol, RNALater). Increasingly over the last decade, these tissue samples have been accessed for uses other than just DNA, including messenger RNA (the expressed form of DNA in cells), proteins, parasites, venoms, toxins and odorant compounds (e.g., Perkins et al, 1998;Nishimura et al, 2012).…”
Section: What Are Voucher Specimens?mentioning
confidence: 99%